Contribuição ao estudo do fosfogesso comparativamente a algumas propriedades do gesso mineral - Brondino, João Ailton (2014)
The phosphogypsum is calcium sulfate (gypsum chemical), generated as waste in industrial production of phosphoric acid, the main raw material for the production of phosphate fertilizers. Is generated on a large scale, and to produce one ton of phosphoric acid are generated many tons of phosphogypsum, depending on the composition of the phosphate rock used. In Brazil are generated annually million tons and disposed in landfill or dumpsites sites without suitable destination for the volume generated, which represents a major environmental liability and worsens, progressively, with the need for increased food production. Thus, this research aimed to determine a relationship between temperature and phosphogypsum the calcination time, to study the possibility of adapting their use in construction. For this, calcined phosphogypsum samples were produced with different combinations of temperature and time, and, then were used in the preparation of the molded specimens. These were evaluated in mechanical tests (compressive strength and tensile strength in bending) and physical (water absorption). The best combination of temperature and calcination time was 159°C and 120 minutes, results that expressed the highest mechanical resistance to bending and compression, and the water absorption index met the Brazilian standards adopted in the recommendations for blocks concrete and blocks ceramic. The scientific contribution of this work will be important not only for building, but for the sustainability of the planet, because an industrial waste that is generated in large quantities, can become raw material for the production of building components for buildings, will avoid the need of new controlled landfill sites for its disposal and also, where an industrial residue replaces a raw material, it is noteworthy that, besides the use and eliminate waste landfills, we will stop exploring the raw material replaced, prolonging the "lifespan" the same and/or preserving of areas exploration.